Kinetics of Mixed Adsorbent Systems in Gas–Solid Adsorption - Paul A. Webley; Richard S. Todd (Adsorption Science & Technology)
Mixtures of solid adsorbents often occur in the process industries through either accident or design. To model such systems, a common approach is to define a pseudo-adsorbent with equilibrium properties equal to the mass fraction weighted average of the components in the mixture. The selection of an appropriate mass-transfer rate constant for the mixture is, however, more complicated. In this study, we have derived simple relationships between the linear driving force rate constants for a pseudo-mixture in terms of the rate constants, equilibrium parameters and mass fractions of the components of the mixture. The reciprocal rate constant for a mixture of adsorbents was shown to be related to the mass fraction weighted average reciprocal rates of the components of the mixture for the case of equal equilibrium isotherms. Expressions of greater complexity resulted for non-linear and non-equal isotherms. Experimental testing was undertaken of the breakthrough behaviour in adsorbent mixtures using the air system with mixtures of CaX and NaX in an adiabatic packed column. The mass-transfer behaviour of the solid mixtures was in good agreement with that predicted by the simple models.